Synthesis of Thioethers by InI3-Catalyzed Substitution of Siloxy Group Using Thiosilanes - Yoshihiro Nishimoto (Molecules, 2016)
The substitution of a siloxy group using thiosilanes smoothly occurred in the presence of InI3 catalyst to yield the corresponding thioethers. InI3 was a specifically effective catalyst in this reaction system, while other typical Lewis acids such as BF3⋅OEt2, AlCl3, and TiCl4 were ineffective. Various silyl ethers such as primary alkyl, secondary alkyl, tertiary alkyl, allylic, benzylic, and propargylic types were applicable. In addition, bulky OSitBuMe2 and OSiiPr3 groups, other than the OSiMe3 group, were successfully substituted. The substitution reaction of enantiopure secondary benzylic silyl ether yielded the corresponding racemic thioether product, which suggested that the reaction of tertiary alkyl, secondary alkyl, benzylic, and propargylic silyl ethers would proceed via a SN1 mechanism.